Morphology-controlled BaTiO3 nanostructures with high sensitivity and fast response for respiratory monitoring. Issue 13 (1st July 2022) - An, Xing-Yan; Zhang, Le-Xi; Xing, Yue; Yin, Yan-Yan; Li, Cheng-Tao; Bie, Li-Jian
Abstract: As a typical perovskite oxide, BaTiO3 has been fully proved to be an excellent impedance humidity sensing material, meanwhile its application in human respiratory monitoring needs to be further researched. In this contribution, BaTiO3 nanorods (BT-NR), nanowires (BT-NW) and micron particle (BT-MP) were successfully synthesized by the molten salt synthesis (MSS) method. Various characterization techniques were used to analyze the structure, morphology and composition of these materials. As-synthesized BaTiO3 samples had been assembled as impedimetric humidity sensors and then tested systematically under relatively humidity (RH) range of 11%–97%. All the three sensors exhibited high response values greater than three orders of magnitude, which are much higher than the commercial BaTiO3 (BT-C) sensor (S97%  = 4.90 × 10 2 ). Thereinto, the BT-NR humidity sensor holds the fastest response-recovery times (1 s and 22 s) and the smallest hysteresis (ΔH = 0.67%). Excellent sensing performance of BT-NR can be attributed to synergistic effects of larger specific surface area and smaller pore size. In addition, the BT-NR humidity sensor shows considerable potential in the field of human respiratory monitoring. This work provides a new perspective to high-performance humidity sensors for human body-related detection through morphology-controlled perovskite nanostructures.